Entrustable professional activities: Towards standardization of language and meaning in Spanish and Portuguese - Melo de Andrade, Marcus Vinicius (2022)
The EPAs approach has had a great impact on medical education since it emerged in 2005. Its dissemination has required translation into several languages, sometimes generating terminological and meaning confusion. This paper is the result of an expert consensus procedure regarding the translation of key terms for understanding the EPA approach in Spanish and Portuguese. It was carried out through a process of meaning analysis of each term in its idiomatic context and of the practice of health professionals training in Latin America. Participated on this consensus by twelve professionals, teachers and scholars involved in the implementation and training with EPAs in eight countries, who participated as coordinator, facilitators or participants in the International Course Ins and Outs of EPAs for Latin America.